2018
DOI: 10.1016/s2213-2600(18)30058-4
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to corticosteroid-induced adrenal suppression: a genome-wide association study

Abstract: SummaryBackgroundA serious adverse effect of corticosteroid therapy is adrenal suppression. Our aim was to identify genetic variants affecting susceptibility to corticosteroid-induced adrenal suppression.MethodsWe enrolled children with asthma who used inhaled corticosteroids as part of their treatment from 25 sites across the UK (discovery cohort), as part of the Pharmacogenetics of Adrenal Suppression with Inhaled Steroids (PASS) study. We included two validation cohorts, one comprising children with asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 28 publications
0
52
0
Order By: Relevance
“…Furthermore, the genomic region encompassing HS1.2 and IGHG3 overlaps entirely with a slightly larger region (90 kb, chr14:106150000–106240000) densely populated with a number of variable SNP sites associated to different phenotypes (Buck et al, ; Goris et al, ; Hawcutt et al, ; Sun et al, ). In particular, two of them were found to be associated with increased levels of Ig G in the cerebrospinal fluid as compared to serum, a hallmark of Multiple Sclerosis (Buck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the genomic region encompassing HS1.2 and IGHG3 overlaps entirely with a slightly larger region (90 kb, chr14:106150000–106240000) densely populated with a number of variable SNP sites associated to different phenotypes (Buck et al, ; Goris et al, ; Hawcutt et al, ; Sun et al, ). In particular, two of them were found to be associated with increased levels of Ig G in the cerebrospinal fluid as compared to serum, a hallmark of Multiple Sclerosis (Buck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies indicate considerable genetic variation in drug‐targeting sites of many G‐protein coupled receptors (GPCRs), which may provide an area of furtive research for the endocrine field . Likewise, another recent study demonstrated asthma patients carrying specific genetic variants in the PDGFR gene were at increased risk of steroid‐induced adrenal suppression . Thus, it is possible that genetic testing may not only be used to guide therapy but also to predict those at increased risk of adverse endocrine outcomes.…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%
“…118 Likewise, another recent study demonstrated asthma patients carrying specific genetic variants in the PDGFR gene were at increased risk of steroid-induced adrenal suppression. 119 Thus, it is possible that genetic testing may not only be used to guide therapy but also to predict those at increased risk of adverse endocrine outcomes.…”
Section: Incidental Findingsmentioning
confidence: 99%
“…For example, a recent genome-wide association study (see table 1) in children with asthma discovered a genetic variation in the platelet-derived growth factor D locus that increased the risk of adrenal suppression in response to steroid therapy 27. This finding will potentially enable risk stratification of patients for more intensive monitoring of adrenal function, as well as encourage use of alternative medications, for example, leukotriene antagonists or anti-IgE therapy in these patients where possible 27…”
Section: A Systems Biology Approachmentioning
confidence: 99%